A Joyful Dialogue with Spinoza and Others: Le Dœuff, Deleuze and the Ethics. Issue 3 (November 2014) - Anderson, Pamela Sue
<x xml:space="preserve">Abstract</x> This essay argues for a Le Dœuffian dialogue with Spinoza's Ethics, intending the increase of affective knowledge and bodily power. This intention requires a striving to learn: first, what perhaps we do not already know; second, what our bodies can do; and third, to increase in joy. From this dialogue the reader can gain Spinozist knowledge of bodies, minds, affections, as well as gaining the power to affect and to be affected by other bodies. One of the features of this Le Dœuffian practice is a collective exploration of what makes dialogue productive and joyful, opening up new possibilities, especially for women in philosophy today.